Analisis Hubungan Karakteristik Ibu Dengan Kejadian Stunting Di Indonesia - Mirin, Anike Novita D.; Lusiani Tjandra; Theodora (Calvaria Medical Journal, 2024)
Introduction: Mothers have an important role in the family, mothers are the heart of the family because mothers play a role in raising and caring for children which influences the child's growth and development. Stunting is a chronic nutritional problem in toddlers which is characterized by shorter height compared to children their age. Globally, the prevalence of stunting is still high, especially in developing countries, including Indonesia. Based on data from the National Nutrition Status Survey (SSGI) and Riskesdas in 2022, the prevalence of stunting in Indonesia is 21.6%, down from 24.4% in 2021. Objective: To analyze the relationship between maternal characteristics and the incidence of stunting in Indonesia. Method: This type of research is a literature review that uses previous research from national and international journals as a reference for drawing conclusions. Results: Of the 25 articles, 17 articles were found discussing maternal characteristics, including 5 articles about maternal height, 10 articles about birth spacing, 7 articles about upper arm circumference, 10 articles about maternal nutritional status and 3 articles about anemia, there were 4 articles about work mothers and 17 articles about maternal education. Conclusion: Maternal characteristics associated with the incidence of stunting are maternal height less than 150 cm, pregnancy interval less than 2 years, maternal upper arm circumference (LILA) below 23.5 cm, mothers with poor nutritional status and anemia, mothers who do not work and low maternal education